Research trends in polio during the last 50 years: a bibliometric analysis - Khan, Muhammad; Ahmad, Tauseef; Khan, Muhammad Mumtaz; Murad, Manal Abdulaziz; Baig, Mukhtiar; Ali, Asmat; Rehman, Abdur (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Many polio cases have been reported in recent years, which strongly affect the Global Polio Eradication Initiative campaign. This study aimed to determine the global trends in polio research during the last fifty years. METHODOLOGY: An online search was conducted utilizing the Web of Science Core Collection database. The key term used was “Polio*" and the retrieved documents were assessed for several attributes. The required graphs were generated using OriginPro 2018. Furthermore, the data were plotted for co-authorship organizations, co-authorship countries, and co-occurrence author keywords network visualization mapping using VOSviewer software for windows. RESULTS: A total of 2,345 publications were included, cited 22,872 times. The year 2017 was the most frequent year with 162 (6.91%) publications. The paper authored by Nomoto and colleagues published in 1977 was the leading paper with 237 citations. In total, Vaccine was the leading journal with 168 (7.16%) publications, followed by Journal of Infectious Diseases 106 (4.52%), and Lancet 77 (3.28%). The included publications were published from 132 countries, of which 44 countries contributed ≥10 publications. The United States of America was the leading country with the highest number of publications (n=740, 31.56%), followed by India (n=215, 9.17%), and England (n=180, 7.68%). CONCLUSION: This study provide researchers and policy makers with a comprehensive list of the key bibliometric characteristics and major contribution in polio research. Majority of the studies were published in developed countries. The developing countries need to make strong research collaborations with developed countries.